Gender and Narrative in the Mahabharata, edited by Simon Brodbeck and Brian Black - Hegarty, James M. (Religions of South Asia, 2010)
Gender and Narrative in the Mahabharata, edited by Simon Brodbeck and Brian Black. London and New York: Routledge, 2007. 326 pp., £95.00 (hb). ISBN 978-0-415-415408-8.